Are Dutch Old-Age Pensions Taxed Fairly and Efficiently? - Bernd Genser; Robert Holzmann (Center for Economic Studies and Ifo Institute (CESifo), 2020)
The Dutch pension system is internationally top-ranked as a well-designed three-pillar system. Moreover, almost all forms of pension benefits are expenditure taxed in line with the European Commission's recommendations. Consequently, the Dutch pension policy approach could be regarded as a welcome blueprint for pension policy reform, currently on the agenda of all EU member countries. This paper focuses on the taxation of Dutch pensions and identifies two classes of problems that challenge the suitability of deferred pension taxation. First, cash flow taxation of pensions erodes the tax equity objectives of a progressive income tax. Second, deferred pension taxation generates a double fairness dilemma in a world with free cross-border migration and double taxation treaties in accordance with the OECD Model Tax Convention. The paper argues that these problems, as well as other minor problems in Dutch pension taxation, could be solved by replacing the Netherlands' current system of deferred income taxation of pensions with a frontloaded expenditure tax system.
Keywords: H24; H55; H87; F22; 330; pension taxation; front-loaded expenditure taxation; progressivity erosion; international migration; OECD model tax convention